The American Civil War in British Culture - Tal, Nimrod. author. aut Link
X, 219 p.
Keywords: This book explores the continuous British fascination with the American Civil War from the 1870s to the present. Analysing the War's place in British political discourse, military writing, intellectual life and popular culture, it traces the sources of Britons' appeal to the American conflict and their use of its representations at home and abroad.